Etiology of obesity - Poh, Bee Koon; Lim, See Meng; Baig, Atif Amin; Chan, Caryn Mei Hsien; Cheah, Yong Kang; Joan, Christine; Mognard, Elise Line; Christelle, Karen; Koo, Hui Chin; Law, Leh Shii; Tung, Serene En Hui; Sharif Ishak, Sharifah Intan Zainun; et al. (Malaysian Association for the Study of Obesity (MASO), 2024)
This chapter explores diverse factors influencing obesity, encompassing both modifiable and non-modifiable elements. Genetic and biological factors, which may be challenging to modify, set the foundation for understanding obesity. The regulation of energy balance, involving dietary intake and physical activities, plays an important role in shaping body composition. Unhealthy dietary habits and insufficient physical activity stand out as crucial contributors to the obesity landscape in Malaysia. The impact of food availability, access, and marketing on obesity is examined. Considering economic influences, the price of food and drinks becomes a key aspect influencing dietary patterns. Discussions on food security highlight potential strategies such as taxes on unhealthy foods and subsidies for healthier options. This chapter also delves into the role of urbanisation and socioeconomics, emphasizing how sociological influences can shape dietary changes. Complementing the exploration of dietary factors, the nation also exhibits low physical activity rates, particularly among women, children, and the elderly. The challenges of urbanisation, technological advancements, and sedentary jobs present formidable obstacles to fostering active lifestyles. Moreover, the chapter also addresses sociological influences, encompassing neighbourhood safety and built environments, which contribute to the complex dynamics on obesity. This comprehensive exploration sets the stage for an in-depth analysis of obesity-related factors, providing a foundational understanding for subsequent sections in this book.